In vivo ctcf and yb-1 interaction with ap-1 site of matrix metalloproteinase 13 gene promoter in human malignant melanoma cell line - Ibrahim, Wisam Nabeel; Abdull Rasad, Mohammad Syaiful Bahari; Abdul Wahab, Ridhwan; Hashim, Ridzwan (2014)
Skin cancer is one of the most common malignancies in young adults. Among all types of skin cancers, malignant melanoma is the most serious tumor in terms of local invasiveness and mortality rate. Matrix metalloproteinase (MMP) family of enzymes are key enzymes responsible for the degradation of extra cellular matrix components and their role in tumor invasion and metastasis has been proven through many studies in many types of cancers. Many MMPs including all collagenases contain AP-1 DNA binding sites in their gene promoters, and they are transcriptionally regulated via this site. CTCF & Yb-1 transcription factors are among the many proteins which can bind specifically to AP-1 site of MMPs promoter gene. This study aimed to detect the interaction between CTCF or YB-1 transcription factors with the AP-1 site of MMP-13 gene promoter. This approach was performed to discover a probable therapeutic pathway through the effect of this protein – DNA interaction on the expression of MMP-13 which is a key factor in the process of malignant melanoma skin cancer invasion